'Can they really identify mental health problems at the age of three?' Parent and practitioner views about screening young children's social and emotional development - Alexander, K.; Brijnath, Bianca; Mazza, D. (Sage Publications Ltd., 2013)
Objective: To report the views of parents, general practitioners and practice nurses on the proposed changes to incorporate social and emotional health checks of three-year-olds into the Healthy Kids Check, a one-off pre-school health assessment delivered through general practice. Method: Participants were recruited from three socio-culturally diverse urban areas of Melbourne for a qualitative study involving 28 parent interviews and six focus groups with a total of 40 practitioners. Participants discussed child social and emotional development, health-seeking and preventive health care for young children. Transcripts were thematically analysed. Results: Common themes showed: (i) Although both parents and practitioners were receptive to the idea of social and emotional screening, parents had limited knowledge about mental health issues for young children and the need for early intervention. (ii) All groups questioned the current capabilities of practice staff to identify problems, and practitioners expressed a need for further training and tools. (iii) Parents and practitioners cautioned that screening may increase parental anxiety and lead to unnecessary referrals. Practitioners countered this with examples of cases not recognised by parents. (iv) Participants questioned the value of earlier identification of problems without effective and accessible therapeutic pathways. Conclusions: For programmes to be effective, parents need to be reminded of the benefits of early intervention and encouraged to attend preventive health appointments. Practitioners require further training and tools specific to the primary care setting. Further investment in specialist and allied health services is considered essential to assure better outcomes for young children's mental health following screening and referral. Practitioners welcome a more collaborative relationship with other professionals (e.g. early educators) in assessing children's social and emotional development. General practice has the capability but requires a more structured approach to assessing the social and emotional health of young children. © 2013 The Royal Australian and New Zealand College of Psychiatrists.